Combination of EGFR-TKIs and chemotherapy in advanced EGFR mutated NSCLC: Review of the literature and future perspectives. (February 2020) - Rebuzzi, Sara Elena; Alfieri, Roberta; La Monica, Silvia; Minari, Roberta; Petronini, Pier Giorgio; Tiseo, Marcello
Highlights: Acquired or intrinsic resistance to EGFR-TKIs develops in EGFR mutated NSCLC. EGFR-TKIs plus chemotherapy strategy has been investigated to delay TKI resistance. Studies of EGFR-TKIs and chemotherapy combination in EGFR mutated patients have shown promising results. Trials of combination of chemotherapy and osimertinib are ongoing. Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) improved clinical outcome compared to chemotherapy in EGFR mutated advanced non-small cell lung cancer (NSCLC) patients. Nonetheless, acquired resistance develops within 10–14 months and 20–30% of EGFR-mutated patients do not respond to EGFR-TKI. In order to delay or overcome acquired resistance to EGFR-TKIs, combination therapies of EGFR-TKIs with chemotherapy has been investigated with conflicting results. Early studies failed to show a survival benefit because of a lack of patient selection, but more recently clinical studies in EGFR mutated patients have shown promising results. This review summarizes preclinical and clinical studies of combination of EGFR-TKIs, including the third-generation TKI osimertinib, with chemotherapy in first- and second-line settings, using concurrent or intercalated treatment strategies. In the new era of third-generation EGFR-TKIs, new studies of this combination strategy are warranted.